Effect of intermittent theta burst stimulation combined with acoustic startle priming motor training on upper limb motor function and neural plasticity in stroke individuals: study protocol for a randomised controlled proof-of-concept trial - Jing Zhang; Yu Chen; Mingzhu Wang; Nan Xia; Jinghong Li; Weiqiang Liang; Yangyang Yin; Linhan Zhai; Qiuxia Wang (BMJ Open)
Introduction Stroke is a major cause of acquired disability globally, yet the neural mechanisms driving motor recovery post-stroke remain elusive. Recent research has underscored the growing significance of subcortical pathways in neural plasticity and motor control. Among these, the cortico-reticulospinal tract (CRST) has gained attention in rehabilitation due to its unique ascending and descending structural features as well as its cellular properties which position it as an excellent candidate to compensate for inadequate motor control post-stroke. However, the optimal strategies to harness the CRST for motor recovery remain unknown. Non-invasive modulation of the CRST presents a promising though challenging, therapeutic opportunity. Acoustic startle priming (ASP) training and intermittent theta burst stimulation (iTBS) are emerging as potential methods to regulate CRST function. This study aims to investigate the feasibility of segmentally modulating the cortico-reticular and reticulospinal tracts through ASP and iTBS while evaluating the resulting therapeutic effects.Methods and analysis This is a randomised, blinded interventional trial with three parallel groups. A total of 36 eligible participants will be randomly assigned to one of three groups: (1) iTBS+ASP group, (2) iTBS+non-ASP group, (3) sham iTBS+ASP group. The trial comprises four phases: baseline assessment, post-first intervention assessment, assessment after 3 weeks of intervention and a 4-week follow-up. The primary outcomes are the changes in the Fugl-Meyer Assessment-Upper Extremity and Modified Ashworth Scale after the 3-week intervention. Secondary outcomes include neurophysiological metrics and neuroimaging results from diffusion tensor imaging and resting-state functional MRI.Ethics and dissemination The trial is registered with the Chinese Clinical Trial Registry (Registration No. ChiCTR2400085220) and Medical Ethics Committee of Tongji Hospital, affiliated with Tongji Medical College, Huazhong University of Science and Technology (Registration No.TJ-IRB20231109). It will be conducted in the Departments of Rehabilitation Medicine and Radiology at Tongji Hospital in Wuhan, China. The findings will be disseminated through peer-reviewed journal publications and presentations at scientific conferences.Trial registration number ChiCTR2400085220.